2002
DOI: 10.1080/00365540110076877
|View full text |Cite
|
Sign up to set email alerts
|

Three Cases of Rothia dentocariosa Bacteraemia: Frequency in Denmark and a Review

Abstract: Three cases of non-endocarditis-associated Rothia dentocariosa bacteraermia occurred in Viborg County within the space of a year, whereas no cases have been registered in other parts of Denmark during the last 10 y. Two patients wore dentures but had no history of oral infection, while in the last patient a tooth abscess was detected on examination. R. dentocariosa is a common inhabitant of the oral cavity and the causative agent of a wide spectrum of infectious symptoms. It is only rarely identified in blood … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
12
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 17 publications
0
12
0
Order By: Relevance
“…The R. aeria strain that we detected was not susceptible to clindamycin or vancomycin, neither of which had been given to the patient. In addition, R. dentocariosa is reportedly not resistant to clindamycin or vancomycin (14); however, Salamon et al reported that the minimum inhibitory concentration (MIC) of vancomycin for a particular strain of R. dentocariosa determined using an Etest is 3 μg/mL (18). If vancomycin, which is usually used in empirical therapy for infective endocarditis caused by Gram-positive organisms, had been prescribed to the patient during hospitalization, the efficacy would have been poor due to the organism's lack of susceptibility to this drug.…”
Section: Discussionmentioning
confidence: 99%
“…The R. aeria strain that we detected was not susceptible to clindamycin or vancomycin, neither of which had been given to the patient. In addition, R. dentocariosa is reportedly not resistant to clindamycin or vancomycin (14); however, Salamon et al reported that the minimum inhibitory concentration (MIC) of vancomycin for a particular strain of R. dentocariosa determined using an Etest is 3 μg/mL (18). If vancomycin, which is usually used in empirical therapy for infective endocarditis caused by Gram-positive organisms, had been prescribed to the patient during hospitalization, the efficacy would have been poor due to the organism's lack of susceptibility to this drug.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent review of R. dentocariosa bacteremia and endocarditis cases, the authors suggested this rarity may be attributed to lack of awareness and inadequate identification methods (12). In the present study, two of eight of charcoal-black-pigmented Rothia-like isolates were from blood specimens, which emphasizes the pathogenic potential of R. dentocariosa.…”
Section: Discussionmentioning
confidence: 62%
“…Most reported cases are due to infections with R. dentocariosa , followed byinfections with R. mucilaginosa . R. dentocariosa has been associated with severediseases such as endocarditis [7] and bacteremia [8], peritonitis (especially in the peritoneal dialysis population)[9], pneumonia [10], septic arthritis [11], and ocular infections such as corneal ulcers [12] and endopthalmitis [13]. R. mucilaginosa is less commonly reported, but has been associated with bacteremia [14], peritonitis [15], meningitis [16], pneumonia [17], and septic arthritis [18].…”
Section: Discussionmentioning
confidence: 99%